Dependence of Platelet Adenyl Cyclase System on Oxidative Phosphorylation - Hashimoto, Shuichi; Shibata, Sachiko; Kobayashi, Bokro (Thrombosis and Haemostasis, 1975)
The radioactive adenosine 3′,5′-monophosphate (cyclic AMP) level derived from 8-14C adenine in intact rabbit platelets decreased in the presence of mitochondrial inhibitor (potassium cyanide) or uncoupler (sodium azide), and markedly increased by the addition of NaF, monoiodoacetic acid (MIA), or 2-deoxy-D-glucose. The stimulative effect of the glycolytic inhibitors was distinctly enhanced by the simultaneous addition of sodium succinate. MIA did neither directly stimulate the adenyl cyclase activity nor inhibit the phosphodiesterase activity. These results suggest that cyclic AMP synthesis in platelets is closely linked to mitochondrial oxidative phosphorylation.